Orchidaceae from Viruá National Park, Roraima, Brazilian Amazon - Pessoa, Edlley M.; de Barros, Fábio; Alves, Marccus (Phytotaxa, 2015)
Viruá National Park is located on the Guyana Shield, an area known for its high levels of biodiversity and endemism. Furthermore, the Brazilian portion of the Guyana Shield is very poorly known, so that floristic studies are needed to know the local distribution of the species. The aim of this study is to survey the species of Orchidaceae from Viruá National Park, Roraima State, Brazil. Orchidaceae are represented in the study area by 67 species and 45 genera. Epidendrum L. (9 spp.) and Catasetum Rich. ex Kunth (5 spp.) are the most diverse genera. These species comprise about 25% of the species and about 50% of the genera cited for the state of Roraima, northern Brazil, and include 19 new species records for the state. The dense forest (“terra-firme” and flooded forests) is more diverse (56 spp.) than the “campinarana” vegetation (13 spp.), and both share only a single species. Descriptions, illustrations, ecological comments, geographical distribution and an identification key are provided.